The Intravascular Generation of Fibrinogen Derivatives and the Blood Vessel Wall in Venous Thrombosis and Disseminated Intravascular Coagulation - Stewart, Gwendolyn J. (Thrombosis and Haemostasis, 1977)
Both deep venous thrombosis and DIC are intermediate mechanisms of disease – both are a consequence of the deposition of fibrin-rich material in blood vessels some distance from the primary site of tissue destruction. The great difference in the sites of fibrin deposition may depend on the extent and site of activation of the clotting mechanism. DIC likely occurs in the fluid phase of the blood as a consequence of massive fibrin formation while thrombosis results from limited fibrin formation at the interface between blood and vessel wall. Leukocytes may be essential for attaching thrombi to the vessel wall in many places.